The Effects of Company Profit and Loss and Type of Industry on the Profitability of PT. Perkebunan Nusantara IV North Sumatra, Indonesia - Sinta, Irada; Ilham, Rico Nur; Nurhasanah, Nurhasanah; Rais, Rany Gesta Putri; Rahmaniar, Rahmaniar (Indonesia Academia Research Society, 2023)
This study determines the effects of company profit and loss and the type of industry on the profitability of PT Perkebunan Nusantara IV North Sumatra. This study used a quantitative method with multiple linear regression equation models to answer the research problems. The results show that the Profit and Loss variable has a positive and significant effect, the type of industry variable has a significant effect, and the Profit and Loss variable and Industry Type have a significant effect simultaneously on the Profitability of PT. Perkebunan Nusantara IV. Companies should be able to increase revenue by reducing costs efficiently so that the profits obtained can increase and financial performance can be better. PT. Perkebunan Nusantara IV has a good profitability ratio. To further increase profits in the following year, the company must be able to manage the capital invested in assets and increase net income to obtain a better net profit.